Rewetting of semi-dried ink patterns by vapour annealing for developing a reflow process in reverse offset printing. (3rd November 2016) - Kusaka, Yasuyuki; Sugihara, Kazuyoshi; Koutake, Masayoshi; Ushijima, Hirobumi
Abstract: A process for reflowing patterned materials for reverse offset printing was developed, with the aim of mitigating the step-coverage problem in multilayered devices. The proposed reflow process involves a single step of vapour annealing at moderate temperatures ranging from 60 to 70 °C. This step successfully changes the height profile of semi-dried ink patterns formed on a silicone blanket, from an initially rectangular shape to a rounded shape. A systematic investigation on the effects of various vapour species and vapour temperatures on the reflow process revealed that the miscibility between the vapour and the ink, and a low boiling point of the respective solvent (high vapour pressure) are the prerequisites for successful reflows of semi-dried ink layers patterned on a silicone blanket. The results suggested that the rewetting of previously semi-dried patterns is the main mechanism in the reflow process, which led to a change in the height profile. Furthermore, the reflowed patterns demonstrated almost identical peak-height thicknesses, irrespective of the width of the patterns. This is a unique property that is unattainable by other printing methods, including gravure offset printing and microcontact printing, wherein printed patterns have rounded shapes without a reflow process, but their thickness inevitably depends on the pattern sizes.